Characteristics of the soil and the seedlings of teak plants submeted to liming sludge - Vieira, Cristiane Ramos; da Silva, Alexsandro Pereira; Weber, Oscarlina Lúcia dos Santos; Scaramuzza, José Fernando (Revista Ecologia e Nutrição Florestal - ENFLO, 2014)
This study aimed to verify to evaluate the growth of T. grandis Linnaeus filius seedlings using as organic substrate and source of nutrient, the sludge lime. The experiment was conducted in a nursery using the treatments: 0.0; 30.0; 60.0; 90.0; 120.0 and 150.0 Mg ha-1 of sludge lime. At the end of the experiment, were analyzed plant height, diameter, shoot and root dry biomass, and chemical soil. It was observed reduced increments in all morphologic characteristics evaluated as the residue is added, and therefore, changed all the chemical characteristics of the soil. The sludge liming in the doses studied was not adequate for the production of T. grandis seedlings.